Extracellular microvesicles-derived from microglia treated with unaggregated α-synuclein attenuate mitochondrial fission and toxicity-induced by Parkinsonian toxin MPP - Li, Na; Wu, Yufeng; Zhu, Liangyi; Huang, Yang; Liu, Zongran; Shi, Min; Soltys, David; Zhang, Jing; Chang, Qing (Biochemical and biophysical research communications, 2019)
Biological functions of extracellular vesicles (EVs) are being discovered to be critical in neurodegenerative disorders, including Parkinson's disease (PD). A previous study using cellular models of PD has suggested that EVs derived from microglia exposed to aggregated α-synuclein (α-Syn) leads to enhanced neurotoxicity. However, the function of EVs derived from microglia not treated with aggregated a-Syn or treated with monomeric α-Syn are unclear. Here, employing a widely used cellular model of PD, i.e. SH-SY5Y cells treated with MPP+, a well-established parkinsonian toxicant, we revealed that microglial EVs, when not stimulated by aggregated α-Syn, appeared to be protective, and the mechanisms, though remain to be defined further, appeared to involve mitochondrial dynamics, especially mitochondrial fission. •MPP+, a parkinsonian toxicant, may induce neuronal cell injury via regulating the SGK1-FOXO3a pathway, promoting generation of reactive oxygen species and inflicting mitochondrial dynamics imbalance, with enhanced mitochondrial fission.•Microglial EVs, isolated from media after treatment with unaggregated α-synuclein, could be internalized by cultured neurons.•EVs isolated from microglia treated with unaggregated α-synuclein attenuated the neurotoxicity.